2017
DOI: 10.1186/s12864-017-4349-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic wounds alter the proteome profile in skin mucus of farmed gilthead seabream

Abstract: BackgroundSkin and its mucus are known to be the first barrier of defence against any external stressors. In fish, skin wounds frequently appear as a result of intensive culture and also some diseases have skin ulcers as external clinical signs. However, there is no information about the changes produced by the wounds in the mucosae. In the present paper, we have studied the alterations in the proteome map of skin mucus of gilthead seabream during healing of experimentally produced chronic wounds by 2-DE follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…In this study, carp keratin I cytoskeletal 18 protein was upregulated (11.4-fold) after I. multifiliis infection, while keratin I cytoskeletal 18-like was downregulated (3.5-fold) at 9 dpe. Keratin has been identified in the skin mucus of gilthead seabream [ 32 ], Atlantic cod [ 33 ], and European sea bass [ 1 ]. Keratin is a cytoskeletal protein whose primary function is to protect cells from mechanical and non-mechanical injuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, carp keratin I cytoskeletal 18 protein was upregulated (11.4-fold) after I. multifiliis infection, while keratin I cytoskeletal 18-like was downregulated (3.5-fold) at 9 dpe. Keratin has been identified in the skin mucus of gilthead seabream [ 32 ], Atlantic cod [ 33 ], and European sea bass [ 1 ]. Keratin is a cytoskeletal protein whose primary function is to protect cells from mechanical and non-mechanical injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin turnover is dependent on the ubiquitin–proteasome pathway, and its expression levels can be altered upon injury. Recently, it has been reported that the expression of keratin I and II was downregulated in cod mucus, following a vibrio infection, and in gilthead seabream in response to chronic wounds [ 1 , 5 ]. The carp keratin I cytoskeletal 18 proteins were differentially regulated after I. multifiliis infection, suggesting they may play different sequential and/or site dependant roles in carp immune response aimed at protection against the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown changes in the skin proteome composition of teleost fish (aquatic vertebrates) in response to infection ( 41 , 42 ), stress ( 43 45 ), wounding ( 46 ), or dietary administration of immunostimulants ( 44 , 45 , 47 ). However, most of these studies adopted a two-dimensional (2-D) gel electrophoresis approach where selected spots were then analyzed by peptide fragment fingerprinting and LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%